PET-CT Evaluation, Scoring and Response Assessment of Hodgkin’s and Non-Hodgkin’s Lymphoma: Observation of a Single Institute - Haque, Md Rezwan Ul; Nusrat, Mariom; Ahmed, Kazi Reazuddin; Das, Sudipto; Rashid, Moontaha Binte; Sultana, Jerin; Khan, Jinia Afrin; Tabassum, Ilteza; Jabin, Zeenat (Bangladesh Journal of Nuclear Medicine, 2025)
Introduction: 18F-Fluorodeoxyglucose Positron Emission Tomography (18F-FDG PET-CT) is a non-invasive imaging technique that combines PET and CT in a single instrument. It detects and measures metabolic activity in cancer cells, providing both anatomical and metabolic information. Whole body 18F-FDG PET-CT plays a vital role in staging, evaluating therapeutic response, excluding relapse, and various stages of management of lymphoma and constitutes a step towards the pursuit of personalized therapies. Patients and methods: This observational study was done in the PET-CT division of the Institute of Nuclear Medicine & Allied Sciences (INMAS), Suhrawardy, between May 2024 and December 2024. A total of 42 patients diagnosed with Hodgkin’s lymphoma (HL) and non-Hodgkin’s lymphoma (NHL) who requested whole-body 18F-FDG PET-CT scans were enrolled in this study. Image findings were analyzed and properly documented in a predesigned format to evaluate the results. Results: A total of 42 lymphoma patients with an average age of 41.11 ± 17.50 years were studied. Histologically diagnosed NHL was seen in 26 patients, and among them, B-cell lymphoma was the most common (84.6%), diffuse large B-cell lymphoma (DLBCL) (42.3%) was the most aggressive, and follicular lymphoma (15.4%) was the most indolent subtypes. HL was diagnosed in 16 patients. Male predominance (78.6%) was observed in both types with relatively early onset in NHL. Cervical lymph nodes appear to be the most commonly affected (78.5%) lymph nodes. Higher Deauville scores among the 42 study subjects reflected the severity of disease. Conclusion: PET-CT is most effective when clinicians, reporting nuclear medicine physicians, and radiologists understand the uses and limitations and participate as a multidisciplinary team for accurate interpretation of baseline and post-treatment scans. Bangladesh J. Nuclear Med. 28(1): 62-67, 2025